Study on corrosion failure prevention of expanded solid expandable tubular. (March 2021) - Shi, Changshuai; Chen, Kailin; Zhu, Xiaohua; Fu, Daqi; Qi, Yuekui; Cheng, Feilong; Li, Jianan
Highlights: Selection two kinds of materials that can be used as a solid expandable tubular. Carrying out the feasibility uniaxial tensile test and laboratory expansion experiment. Research the SET corrosion ratio in two kinds of formation water environment. Compare the microstructure and corrosion products of the two materials. Abstract: The solid expandable tubular (SET), as a casing damaged well repair tool, should resist residual stress and liquid corrosion. The objective of this study is to reveal the SET expansion of mechanical properties and anti-corrosion performance to carry out a feasibility laboratory expansion experiment. The materials used in this study are 20G and 316L. The mechanical properties of the expansion process of materials and the corrosion behavior of the tube in two kinds of the simulated formation water environment are investigated. Scanning electron microscope (SEM)-energy spectrometer (EDS) comparative analysis displays the surface microstructure and corrosion products of the two materials in different corrosive environments. The results show that both SET materials can meet the requirements of 5–1/2in casing subsidy. The corrosion rate of 20G is similar, which is equivalent to reducing the thickness by 0.25 mm every 10 years, and the 316L corrosion rate is about one-fifth of 20G. The corroded surfaces of 20G and N80 are multi-crack brittle scales caused by iron oxidation. The surface of 316L has attachments without apparent corrosion. Compared with the N80 shell material, the corrosion product film of 20G is denser and has better corrosion resistance. The corrosion resistance of 316L SET is the strongest among these three materials and is suitable for harsh right conditions in corrosive environments.